Prevalence of Acetabular Dysplasia and its Associated Factors: Major Determinants of Hip Function: Acetabular dysplasia effect on hip joint function (Nigerian Journal of Physiological Sciences, 2025)
SUMMARYThe hip joint bears a considerable proportion of the human weight and the ability to efficiently perform its plethora of functions depends on the status of the acetabulum. Morphological alteration of the acetabulum results in acetabular dysplasia which adversely affects the hip joint. The objectives of this study were to determine acetabular morphology, factors that are associated with acetabular dysplasia which compromise hip joint functions and the prevalence of acetabular dysplasia in apparently healthy adults in Calabar. This prospective cross-sectional study was carried out in the Radiology department of the University of Calabar teaching hospital, Calabar, Nigeria over a 5-months period and involved 100 apparently healthy subjects. Pelvic radiographs were conducted for all the subjects and afterwards center edge angle of Wiberg and acetabular angle of Sharp evaluations were done on all the images on a direct digital radiography viewer. Chi square, T-test and Pearson’s correlation were used to analyze the data. Mean center edge angle of Wiberg and acetabular angle of Sharp were 27.41 ± 0.730 (SEM) and 39.00±0.860 (SEM) respectively. Center edge angle of Wiberg and acetabular angle of Sharp were significantly associated with age (P=0.000 & P=0.000), marital status (P=0.002 & P=0.000) and employment status (P=0.001 & P=0.002). BMI was only significantly associated with center edge angle of Wiberg (P=0.004). Abnormal center edge angle of Wiberg and acetabular angle of Sharp were mostly seen in individuals below 40 years (64% & 88%, respectively), married (65% & 63%, respectively) and employed (75% & 53%, respectively). Most of the individuals with BMI above 25 had abnormal center edge angle of Wiberg (62%). Mean BMI in males was significantly greater than that of females (P=0.000). Acetabular dysplasia was noted in 4 males (4%). It is concluded that the center edge angle of Wiberg and the acetabular angle of Sharp in our population are similar to the values in some European and Asian populations, and the prevalence of acetabular dysplasia is 4% in this locality. Being a male that is married, employed, overweight and below 40 years are significantly associated with acetabular dysplasia and by implication are determinants of hip joint function.